1992
DOI: 10.1128/jb.174.4.1403-1409.1992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of Clostridium cellulovorans endoglucanases-xylanases EngB and EngD hyperexpressed in Escherichia coli

Abstract: By the use of a T7 expression system, endoglucanases-xylanases EngB and EngD from Clostridium ceflulovorans were hyperexpressed and purified from Escherichia coli. The two enzymes demonstrated both endoglucanase and xylanase activities. The substrate specificities of both endoglucanases were similar except that EngD had four-times-greater p-nitrophenyl 13-1,4-cellobiosidase activity. The two proteins were very homologous (80%o) up to the Pro-Thr-Thr region which divided the protein into -NH2-and -COOH-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 34 publications
(45 reference statements)
1
36
0
Order By: Relevance
“…We were not successful in determining the N-terminal amino acid sequence of the polypeptide corresponding to X2, since it occurred in very low quantities. In previous work, we have cloned the genes for C. cellulovorans EngB and EngD, which have not only CMCase activity but also xylanase activity (9,10,14). Although the deduced molecular masses for EngB (48 kDa) and EngD (50 kDa) are close to that of X2, X2 has no CMCase activity (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…We were not successful in determining the N-terminal amino acid sequence of the polypeptide corresponding to X2, since it occurred in very low quantities. In previous work, we have cloned the genes for C. cellulovorans EngB and EngD, which have not only CMCase activity but also xylanase activity (9,10,14). Although the deduced molecular masses for EngB (48 kDa) and EngD (50 kDa) are close to that of X2, X2 has no CMCase activity (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme complex was reported to be very hydrophobic and formed membrane protuberances on the cell surface (12). Previously, we reported the cloning of the engB (1) and engD (7) genes and the characterization of endoglucanase B (EngB) and EngD, which are associated with CbpA in the enzyme complex (2). Furthermore, we reported the cloning and sequencing of the gene for the largest nonenzymatic subunit, CbpA (16).…”
mentioning
confidence: 99%
“…CBM2a has an extra loop containing eight amino acids that is not found in CBM2b. The amino acid sequence of CBM2 of SaGH74A showed high similarity with that of CBM2a in C. fimi and C. cellulovorans (10,24), and three Trp residues in CBM2a which are involved in substrate binding are completely conserved in CBM2 of SaGH74A (26). The results of the binding assay and affinity gel electrophoresis in our study showed that the CBM2 of SaGH74A had an affinity for soluble ␤-1,4-glucan chains but not for insoluble and crystalline substrates.…”
Section: Discussionmentioning
confidence: 57%